Exploring the evidence-practice gap in the use of plain radiography for acute abdominal pain and intestinal obstruction: a systematic review and meta-analysis. Issue 2 (June 2020) - Denham, Gary; Smith, Tony; James, Daphne; McKiernan, Sharmaine; Evans, Tiffany-Jane
ABSTRACT: Aim: Previous studies, some dating back several decades, have recommended that the use of plain abdominal radiography should be curbed, particularly with the growth of more accurate imaging modalities. However, evidence from referral data suggests that plain abdominal radiography continues to be a commonly requested examination. The aim of this review was to explore the gap between evidence and practice by re-examining the evidence using a robust methodology, investigating the diagnostic accuracy of plain abdominal radiography. Methods: Studies were identified from electronic databases and reference lists. Eligible studies provided data as to the sensitivity and specificity of plain abdominal radiography for either acute abdominal pain (Group A) or suspected intestinal obstruction (Group B). Version 2 of the Quality Assessment of Diagnostic Accuracy Studies was used to assess the quality of studies and hierarchical summary receiver operator characteristic curves and coupled forest plots were generated. Results: Four studies evaluated plain abdominal radiography for acute abdominal pain (Group A) and 10 for suspected intestinal obstruction (Group B). Two studies investigated both presentations and were included in both groups. Methodological quality of studies was moderately high, though incorporation bias was a common limitation. Sensitivity for Group A studies ranged from 30 to 46%, with specificity from 75 to 88%. For Group B, the range of sensitivity was 48 to 96% and specificity from 50 to 100%. Conclusion: The results suggest that use of plain abdominal radiography could be substantially reduced, particularly for patients with undifferentiated acute abdominal pain. While some guidelines exist, there is sound argument for clinical decision rules for abdominal imaging to inform evidence-based clinical decision-making and radiology referrals.